Subacromial Spacer Implantation During Arthroscopic Partial Repair in Patients With Massive Irreparable Rotator Cuff Tears Provides Satisfactory Clinical and Radiographic Outcomes: A Retrospective Comparative Study - Kerem Bilsel, M.D; Orkhan Aliyev, M.D; Burak Altintas, M.D; Syed Dil Bagh Ali Shah, M.D; Rodi Ertogrul, M.D; Mehmet Kapicioglu, M.D (Elsevier, 2022)
Purpose: To compare the clinical and radiographic outcomes of partial rotator cuff repair (RCR) with and without implantation of a biodegradable subacromial spacer in the treatment of symptomatic irreparable massive rotator cuff tears (MRCTs). Methods: Patients with MRCT who underwent arthroscopic partial repair alone (PR) or combined with subacromial spacer augmentation (PRS) were included. Patient-reported outcomes, including visual analog scale (VAS), American Shoulder and Elbow Surgeons (ASES), and Constant scores in addition to range of motion (ROM) were collected preoperatively and at the final follow-up. Additionally, we determined the percentages of all of the patients in groups that achieved the minimal clinical important difference (MCID), substantial clinical benefit (SCB), and patient-acceptable symptomatic state (PASS) for the VAS, ASES, and Constant scores. Acromiohumeral distance (AHD) was determined as well. Results: A total of 32 patients were included. Group PR included 20 patients with a median age of 68 years (range: 64-73) and median follow-up 28.0 months (14.0-60.0). Group PRS included 12 patients with a median age of 68.5 years (range: 63-74) and median follow-up of 17.0 months (12.0-32.0). At the final follow-up, the ASES, VAS, and Constant scores were significantly higher in the PRS group (75.5 [55-88.3], 1.0 [0-3], and 70.0 [43-79], respectively, compared to the PR group (55.0 [37.5-65], 2.0 [0-4], and 55.0 [31-79], respectively; P < .05). The only statistically significant differences were found between the PR and PRS groups in terms of the proportions of the patients who achieved MCID for the ASES (70% vs. 100%; P = .04) and in terms of the proportions of the patients who achieved SCB for the ASES (60% vs 100%; P = .01) There was also statistically significant difference between the PR and PRS groups, in terms of the proportions of the patients who achieved PASS for the VAS and ASES ([30 % vs 66.7 %; P = .04] and [0 % vs 50 %; P = .001], respectively). AHD was also improved in the PRS group (8.4 [7-9.5] vs 7.85 [5.5-9]; P < .05). ROM was greater in the PRS group at final follow-up with median forward flexion degree, 140.0° (90°-150°) versus 120.0° (80°-153°) (P < .001) and median abduction degree, 100.0° (70°-130°) versus 90.0° (70°-110°). There was no difference in terms of external rotation between groups (3° [2°-5°] vs 3.0° (2°-4°); P = .4). Conclusions: Arthroscopic partial RCR with implantation of a subacromial spacer leads to satisfactory clinical and radiographic outcomes in patients with symptomatic irreparable MRCT compared with patients treated with partial repair alone. Level of Evidence: Level III, retrospective comparative study.